Exercise Training Attenuates Hypertension Through TLR4/MyD88/NF-κB Signaling in the Hypothalamic Paraventricular Nucleus - Qi, Jie; Yu, Xiao-Jing; Fu, Li-Yan; Liu, Kai-Li; Gao, Tian-Tian; Tu, Jia-Wei; Kang, Kai B.; Shi, Xiao-Lian; Li, Hong-Bao; Li, Ying; Kang, Yu-Ming (Frontiers in Neuroscience, 2019)
Exercise training (ExT) is beneficial for cardiovascular health, yet the central mechanism by which ExT attenuates the hypertensive responses remains unclear. Activation of pro-inflammatory cytokines (PICs) in the hypothalamic paraventricular nucleus (PVN) is important for the sympathoexcitation and hypertensive response. We thus hypothesized that ExT can decrease the blood pressure of hypertensive rats by reducing the levels of PICs through TLR4/MyD88/NF-κB signaling within the PVN. To examine this hypothesis, two-kidney-one-clip (2K1C) renovascular hypertensive rats were assigned to two groups: sedentary or exercise training and examined for eight weeks. At the same time, bilateral PVN infusion of vehicle or TAK242, a TLR4 inhibitor, was performed on both groups. As a result, the systolic blood pressure (SBP), renal sympathetic nerve activity (RSNA) and plasma levels of norepinephrine (NE), epinephrine (EPI) were found significantly increased in 2K1C hypertensive rats. These rats also had higher levels of Fra-like activity, NF-κB p65 activity, TLR4, MyD88, IL-1β and TNF-α in the PVN than SHAM rats. Eight weeks of ExT attenuated the RSNA and SBP, repressed the NF-κB p65 activity, and reduced the increase of plasma levels of NE, EPI, and the expression of Fra-like, TLR4, MyD88, IL-1β and TNF-α in the PVN of 2K1C rats. These findings are highly similar to the results in 2K1C rats with bilateral PVN infusions of TLR4 inhibitor (TAK242). This suggests that eight weeks of ExT may decrease blood pressure in hypertensive rats by reducing the PICs activation through TLR4/MyD88/NF-κB signaling within the PVN, and thus delays the progression of 2K1C renovascular hypertension.